Understanding the needs of MENA public transport customers: Culture of service and gender-responsive recommendations - Delatte, Aline; Baouni, Tahar; Belwal, Rakesh; Daou, Lindos; Gourram, Dounia; Imam, Rana; Safar Zitoun, Madani; Smadi, Ayman (TeMA - Journal of Land Use, Mobility and Environment, 2018)
Fast population growth, urban sprawl and the raise in households’ motorization observed in all major cities of the Middle-East and North-Africa (MENA) region, are constantly challenging public transport providers who seek to handle efficiently the continuously rising travel demand. Most of the MENA cities suffer from traffic congestion that not only impacts the quality of life of MENA citizens, but also their access to job opportunities, health services, and social and political participation. Alongside the development of public transport network, it is crucial to encourage urban dwellers to reduce their dependence on personal cars, use public transport, and develop soft mobility skills. Therefore, operators and service providers need to define customer-centric strategy and build a culture of service excellence in line with their customers’ expectations. In cooperation with academic partners, the UITP MENA Centre for Transport Excellence launched the User-Oriented Public Transport research project with the aim to understand the perceptions of female and male users and non-users about public transport services in five MENA cities: Algiers, Amman, Beirut, Casablanca and Muscat. The methodological framework was built around the five dimensions of the user’s needs pyramid: safety, security, ease-to-use, comfort and experience. Based on the quantitative analysis of data collected from 984 respondents and the qualitative analysis of 49 women’s testimonies collected during the focus groups, recommendations were made to encourage culture of service and gender mainstreaming in public transport development in the region.